PENGARUH LKS IPA TERPADU BERMUATAN LITERASI TEMA GERAK DALAM MODEL PEMBELAJARAN KONTEKSTUAL ADAPTIF TERHADAP KOMPETENSI SISWA KELAS VIII SMPN 15 PADANG - Dwiyan Hari Ramadhan; Djusmaini Djamas; Asrizal Asrizal (Universitas Negeri Padang, 2018)
Integrated science teaching should be implemented well in Junior High School. In addition, school literacy movement needs to be developed to improve literacy of students. But the real conditions show that the integration of science teaching material and literacy of students were still low. The solution of this problem was to use the integrated science student worksheet by integrating digital age literacy in adaptive contextual teaching model. The purpose of the research was to investigate the influence of integrated science student worksheet by integrating the digital age literacy on motion theme in our live toward the competence of grade VIII students in SMPN 15 Padang. The type of research which conducted was quasi-experimental research. The research design was randomized control-group only design. The research population was all students of grade VIII SMPN 15 Padang which registered in academic year in 2017/2018. Sampling technique in this research was purposive sampling. The samples in this research were grade VIII 5 students as the experimental group and grade VIII 7 students as the control group with the total of samples were 64 students. The research instruments consist of observation sheet to assess attitudes, test result sheet to assess knowledge, and performance assessment sheet to assess skill of student. Research data were analyzed by using descriptive analysis and comparison test. From the analysis of data can be stated that the use of Integrated science student worksheet by integrating the digital age literacy of motion theme in our life in adaptive contextual teaching model gives a significant effect on the knowledge, the attitude and the skills competences of grade VIII students in SMPN 15 Padang at 95% confidence level.